Tokyo Olympics 2020: Between dream and contention. Issue 1 (2nd January 2023) - Chiavacci, David; Wieczorek, Iris
ABSTRACT: What was and what will remain of the Tokyo 2020/2021 Olympic and Paralympic Games? This special issue brings together assessments from different perspectives regarding diverse aspects of the impact and legacy of Tokyo's second Summer Olympics. It is safe to say that Tokyo 2020/2021, as the COVID-19 games, did not fully achieve what the Japanese organizers had hoped it would. On the contrary, the Olympic dream of 2020 was postponed and met quite substantial opposition. This introduction discusses the main findings of the contributions and places them in the larger context. The focus is on four aspects of Tokyo 2020/2021: 1) the Olympics as a political project of the conservative establishment and former Prime Minister Abe Shinzō; 2) critical perspectives on the Olympics as a mega event; 3) social movements and protests against the Olympics; 4) impact of the Olympics on technological innovation and city infrastructure.